Microbial-Based Therapies in the Treatment of Inflammatory Bowel Disease – An Overview of Human Studies - Basso, Paulo José; Câmara, Niels Olsen Saraiva; Sales-Campos, Helioswilton (Frontiers in Pharmacology, 2019)
Inflammatory bowel disease (IBD) is a group of multifactorial and inflammatory infirmities comprised by two main entities: Ulcerative colitis (UC) and Crohn’s disease (CD). Classic strategies to treat IBD are focused on decreasing inflammation besides of inducing and extending disease remission. However, these approaches have several limitations such as low responsiveness, excessive immunosuppression and refractoriness. Despite the multifactorial causality of IBD, immune disturbances and intestinal dysbiosis have been suggested as the central players in disease pathogenesis. Hence, therapies aiming at modulating such aspects may represent a promising strategy in IBD control. Fecal microbiota transplantation (FMT) and probiotics have been explored as promising candidates to reestablish microbial balance in immune-mediated diseases such as IBD. These microbial-based therapies have demonstrated the ability of reducing both the dysbiotic environment and production of inflammatory mediators, thus inducing remission, especially in UC. Despite these promising results, there is still no consensus on the relevance of such treatments in IBD. Thus, this review aims to critically review and describe the use of FMT and probiotics to treat patients with IBD.